Hans Mol and the Empirical Study of Australian Religion: Revisiting the 1966 Religion in Australia Survey - Singleton, Andrew (Journal for the Academic Study of Religion, 2023)
This article examines the Religion in Australia survey (RIA) that was conducted in 1966. Led by sociologist Hans Mol, this was the first major survey of religion in Australia. Mol’s findings were published in his landmark monograph, Religion in Australia (1971), which is arguably the most comprehensive work ever written on the religious lives of Australians. To reveal the varieties of Christian belief and practice, Mol developed a typology that categorised Australians into different kinds of believers (not unbelievers). However, Mol’s efforts were circumscribed by the computational, statistical and practical limitations of the time, and he barely engaged with the secularisation literature or other social developments. Using cutting-edge statistical procedures (latent class analysis), this article re-examines Mol’s empirical study of Australian religion and offers deeper and more complex insights into the ‘religious patterns of the Australian population’ in the 1960s. The article highlights Mol’s pioneering empirical sociology of religion and the contribution that he made to the understanding of post-war religion in Australia.